Promoting and Developing Industrial Organic Clusters in Egypt: Case Study of Damietta Furniture Cluster - Abdelmoula, Nermen (AUC Knowledge Fountain, 2024)
This study examines the development of industrial clusters in Egypt, with a specific focus on the Damietta Furniture Cluster, an organic industrial cluster known for its rich tradition in furniture craftsmanship. These industrial clusters, which are primarily composed of micro, small, and medium enterprises (MSMEs), are characterized by the geographical concentration of interconnected firms and institutions, play a critical role in fostering economic growth, innovation, and competitiveness, particularly in emerging economies. The research explores the key factors affecting the development of the Damietta Furniture Cluster, identifies the challenges it faces, and provides policy recommendations to enhance its growth and global competitiveness. The study employs a qualitative research approach, utilizing 14 in-depth interviews with key stakeholders, including government officials, business owners, and representatives from support organizations. The findings highlight the cluster's strengths, such as its deep-rooted craftsmanship and a strong network of micro, small, and medium enterprises (MSMEs). However, the cluster also faces significant challenges, including limited access to finance, outdated infrastructure, and the need for technological upgrades. These challenges are compounded by a restrictive legislative and regulatory environment, fragmentation among support organizations, and fluctuating prices for raw materials. Based on the data analysis and findings, the study suggests various policy recommendations that build upon previous and current efforts and initiatives. Addressing these challenges is essential to unlocking the Damietta Furniture Cluster's full potential and ensuring its sustainable growth in the global market. This study contributes to the broader understanding of industrial clusters development in developing economies and offers practical insights for policymakers and stakeholders involved in the economic development of Egypt. Future research could expand on these findings by exploring comparative studies with other clusters in Egypt or similar contexts globally.